Importance of Long-Term Shallow Degassing of Basaltic Magma on the Genesis of Massive Felsic Magma Reservoirs: a Case Study of Aso Caldera, Kyushu, Japan. (1st February 2023) - Miyagi, Isoji; Hoshizumi, Hideo; Suda, Taichi; Saito, Genji; Miyabuchi, Yasuo; Geshi, Nobuo
Abstract: This paper presents the chemical composition (including H2 O and CO2 ) of matrix glass, melt inclusions in phenocrysts, and their host minerals in eruptive products from Aso caldera. We found a group of melt inclusions with clearly lower potassium (0.6–2 wt % K2 O at 50–70 wt % SiO2 ) than previously reported high-K2 O whole-rock compositions (3–5 wt % K2 O at 55–70 wt % SiO2 ). While most of the high-K2 O intermediate to felsic melt inclusions are vapor undersaturated and show the features of H2 O, CO2, and K2 O accumulation, the low-K2 O basaltic melt already has higher H2 O and CO2 . We reconcile this discrepancy with a model in which (1) the volatile-rich basalt magmas degas near the surface, (2) migrate back to depths of $\ge$ 12 km in the crust, and (3) crystallize feldspar and quartz to produce high-K2 O felsic melt, (4) magma mixing among the undegassed, degassed, and evolved magmas. By crystallization, about five times as much low-K2 O basaltic magma is required to produce high-K2 O felsic magma. The quantity of felsic magma ejected from 270 ka (Aso-1) to 90 ka (Aso-4) requires a basalt magma supply rate of 18 to 31 km 3 /ka. This magma supply rate is comparable to or less than the present-day production rate of degassed magma (73 km 3 /ka) at an active center of Aso, Nakadake. These findings suggest volcanic gas flux monitoring has the potential to be a 'basalt usage meter' during the dormant period of caldera volcanoes.